MiR-135a-5p suppresses trophoblast proliferative, migratory, invasive, and angiogenic activity in the context of unexplained spontaneous abortion - Yebin Lu; Xiaoli Zhang; Xueyu Li; Lingjie Deng; Changqiang Wei; Dongmei Yang; Xuemei Tan; Weicheng Pan; Lihong Pang (BMC, 2022)
Abstract Background Spontaneous abortions (SA) is amongst the most common complications associated with pregnancy in humans, and the underlying causes cannot be identified in roughly half of SA cases. We found miR-135a-5p to be significantly upregulated in SA-associated villus tissues, yet the function it plays in this context has yet to be clarified. This study explored the function of miR-135a-5p and its potential as a biomarker for unexplained SA. Method RT-qPCR was employed for appraising miR-135a-5p expression within villus tissues with its clinical diagnostic values being assessed using ROC curves. The effects of miR-135a-5p in HTR-8/SVneo cells were analyzed via wound healing, Transwell, flow cytometry, EdU, CCK-8, and tube formation assays. Moreover, protein expression was examined via Western blotting, and interactions between miR-135a-5p and PTPN1 were explored through RIP-PCR, bioinformatics analyses and luciferase reporter assays. Results Relative to normal pregnancy (NP), villus tissue samples from pregnancies that ended in unexplained sporadic miscarriage (USM) or unexplained recurrent SA (URSA) exhibited miR-135a-5p upregulation. When this miRNA was overexpressed in HTR-8/SVneo cells, their migration, proliferation, and cell cycle progression were suppressed, as were their tube forming and invasive activities. miR-135a-5p over-expression also downregulated the protein level of cyclins, PTPN1, MMP2 and MMP9. In RIP-PCR assays, the Ago2 protein exhibited significant miR-135a-5p and PTPN1 mRNA enrichment, and dual-luciferase reporter assays indicated PTPN1 to be a bona fide miR-135a-5p target gene within HTR-8/SVneo cells. Conclusion miR-135a-5p may suppress trophoblast migratory, invasive, proliferative, and angiogenic activity via targeting PTPN1, and it may thus offer value as a biomarker for unexplained SA.